(untitled) (Itinerarios Educativos, 2025)
This paper focuses on analyzing the life trajectories of graduates of secondary technical–vocational education in Argentina by generating a structural and articulated typology of the post–graduation period. Specifically, it seeks an approach to this panorama through a study of social stratification in two areas where TVE was supposed to provide advantages: the educational system and the labor market. To do so, it analyzes the characteristics of their homes of origin, their educational trajectories, and their first job. The data in the article is secondary and come from a panel study that for 8 years (2009, 2011, 2013 and 2017) surveyed a probabilistic sample of students and then graduates of state technical schools in Argentina. The typological model was built from a multivariate analysis based on the application of a factor analysis and a subsequent automatic classification analysis. This process resulted in the identification of three typical groups distributed in the social space that account for the intersection of social inequalities of origin, educational trajectories and first employment, producing paths where young people combine advantages and disadvantages in the course of life.